Cardiac rehabilitation do not diminish the socioeconomic and ethnical disparity in patients with coronary heart disease. (14th October 2021) - Kjesbu, I; Prescott, E; Rasmusen, H K; Osler, M; Larsen, M L; Gustafsson, I; Zwisler, A D; Sibilitz, K L
Abstract: Aims: Cardiac patients with low socioeconomic status and non-western ethnic background have worse outcomes. The aim of this nationwide study was to determine whether the immediate effect of CR differs between groups defined by socioeconomic status and ethnic background, and whether disparity in the prognosis of cardiac patients is diminished by CR participation. Methods: We included all patients in Denmark with myocardial infarction and/or coronary revascularization from August 2015 until March 2018. Level of education, as a marker for socioeconomic status, was divided into four groups, and ethnicity into Danish, non-Western and Western. Participation in CR was identified through the Danish Cardiac Rehabilitation Database (DHRD) and the Danish National Patient Register. Primary outcome was achievement of CR quality indicators, including risk factor control and medication, from DHRD, and secondary outcome a composite endpoint of cardiovascular disease hospitalization and all-cause mortality (MACE). Results: We identified 34, 511 patients of whom 19, 383 had participated in CR and 9, 882 provided information on CR data from DHRD. Higher education was associated with greater improvement in VO2peak and non-western patients were less likely to be screened for depression or receive dietary consulting. No other significant disparity in CR quality indicators, was found across education and ethnicity. There was a strong socioeconomic gradient in MACE irrespective of CR participation, medication and risk factor control (adjusted HR 0.71 (0.58–0.86) for high versus low education). Similarly, non-western origin was associated with higher risk of MACE (adjusted HR 1.2 (1.1–1.4). Conclusion: We found strong socioeconomic and ethnic disparity in prognosis of CHD patients which were unaffected by CR participation. The results indicate that CR, conventional risk factor control and medical treatment have limited impact on these disparities. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): The Danish Heart Foundation